2023
DOI: 10.1002/mabi.202200539
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mechanical Properties of Hydrogels for Cartilage Tissue Defect Repair

Abstract: Numerous factors, such as degeneration and accidents, frequently cause cartilage deterioration. Owing to the absence of blood vessels and nerves in cartilage tissue, the ability of cartilage tissue to heal itself after an injury is relatively low. Hydrogels are beneficial for cartilage tissue engineering owing to their cartilage‐like structure and advantageous properties. Due to the disruption of its mechanical structure, the bearing capacity and shock absorption of cartilage are diminished. The tissue should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…37,38 The repeated compression cycle tests of 4%PUD materials indicated that the performance remained stable even after multiple compressions, and the mechanical properties of 4%PUD closely resembled those of normal cartilage tissue, which explains why the 4%PUD@ HA/PEEK scaffold exhibited the best cartilage repair in animal experiments to some extent. 39 Here, we could see a slight trend that the 4% PUD@HA/ PEEK scaffold is superior to the 8% PUD@HA/PEEK scaffold for OCD repair. In the 4% PUD@HA/PEEK scaffold, the superficial cartilage defects were filled with more regenerated cartilage tissue but were still far from the native cartilage.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…37,38 The repeated compression cycle tests of 4%PUD materials indicated that the performance remained stable even after multiple compressions, and the mechanical properties of 4%PUD closely resembled those of normal cartilage tissue, which explains why the 4%PUD@ HA/PEEK scaffold exhibited the best cartilage repair in animal experiments to some extent. 39 Here, we could see a slight trend that the 4% PUD@HA/ PEEK scaffold is superior to the 8% PUD@HA/PEEK scaffold for OCD repair. In the 4% PUD@HA/PEEK scaffold, the superficial cartilage defects were filled with more regenerated cartilage tissue but were still far from the native cartilage.…”
Section: Discussionmentioning
confidence: 72%
“…This could explain the lower repair ability of high concentrations of PUD in cartilage defects. Furthermore, PUD exhibited a lower swelling rate at 4% concentration, which decreased with increasing concentration at 6–10%, possibly because of variation in porosity. , The repeated compression cycle tests of 4%PUD materials indicated that the performance remained stable even after multiple compressions, and the mechanical properties of 4%PUD closely resembled those of normal cartilage tissue, which explains why the 4%PUD@HA/PEEK scaffold exhibited the best cartilage repair in animal experiments to some extent …”
Section: Discussionmentioning
confidence: 99%
“…23 In the field of bone and cartilage tissue engineering, it is necessary for hydrogels to have mechanical strength comparable to those of natural bone and cartilage to improve the quality of repair. 24 The elastic modulus of articular cartilage can reach up to 950 kPa, while that of bone is even higher than 1 MPa. 97 Unfortunately, CD-based supramolecular hydrogels typically fail to achieve such high mechanical strength values due mainly to the following three factors, (i) the crosslinking of supramolecular hydrogels is primarily based on the reversible non-covalent interactions, (ii) the low grafting efficiency of the host and guest molecules onto the polymer chain results in a low cross-linking density, and (iii) the steric hindrance of the polymer backbone also accounts somewhat for the compromised mechanical properties of the hydrogels.…”
Section: Strategies To Improve the Mechanical Properties Of Cd-based ...mentioning
confidence: 99%
“…23 High-strength supramolecular hydrogels can provide mechanical support in bone/cartilage repair. 24 Hydrogels with favorable mechanical strength enable more controllable, stable, and effective drug delivery. Furthermore, the appropriate drug loading and release modalities of supramolecular hydrogels are crucial for the effective treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…While some hydrogels can be engineered for specic mechanical strengths, many naturally derived hydrogels lack the robustness and durability required for certain bio-applications, especially in load-bearing tissues like cartilage or bone. 20 One of the effective procedures to reinforce hydrogels from a mechanical point of view is proposed to be the integration of bers into a hydrogel network. 21,22 The electrospinning technique is a well-established method for fabricating brous biomaterials and has been widely studied by numerous research groups.…”
Section: Introductionmentioning
confidence: 99%